ANALISIS MITIGASI BENCANA BANJIR DI KOTA TANGERANG SELATAN - Muhamad Taslim; Ahmad Jamil Pasaribu; Azhari Aziz Samudra (LPSDI Bina Patria, 2024)
Safe and disaster-resistant residential areas are an urgent need to reduce disaster risk. The role of the government, especially the South Tangerang City Regional Disaster Management Agency (BPBD), is very important in increasing community preparedness in a comprehensive and targeted manner. In this research, we used a qualitative method by utilizing the study literature scheme as a secondary and primary data source obtained from Scopus, Google Scholar, books, performance reports and annual final reports. Our research results show that South Tangerang City has adopted various measures to reduce disaster risk, especially through disaster risk reduction information. The government has implemented mitigation efforts, such as disaster simulations and disseminating mitigation messages through mass media and social media. Apart from that, the government is also making other persuasive efforts to change people's mindsets in realizing a culture of safety, including through habituation and increasing preparedness in disaster prevention. In this context, residential areas that dominate the spatial layout and have different facilities are the main focus. Risk zoning can be done to divide residential areas into zones with different levels of disaster risk, thereby enabling appropriate spatial planning. Early warning infrastructure also needs to be installed to provide residents with information about impending disasters and allow sufficient time to take necessary actions. Clear and well-identified evacuation routes should be provided, while green open spaces can act as